Exploring nutritive profile, metabolizable energy, protein, and digestible amino acids contents of indigenous protein sources of different locations for male broilers. (25th April 2019) - Azam, F; Qaisrani, S N; Khalique, A; Bibi, F; Akram, C A; Naveed, S; Pasha, T N
Abstract: 2 experiments were conducted to explore nutrient composition, AME, AMEn, standardized ileal digestibility (SID ) of CP, and amino acids (AA ) of 4 indigenous protein sources including canola meal (CM ), rapeseed meal (RSM ), guar meal (GM ), and sunflower meal (SFM ) collected from 2 different locations, Multan (MUL ; n = 3) and Sukkur (SKR ; n = 3), of Pakistan. Higher ( P < 0.05) dry matter (DM ), CP, and gross energy (GE ), whereas lower ( P < 0.05) ash contents were found in SKR, CM, and RSM compared with those from MUL. The MUL GM had higher ( P < 0.05) crude fiber (CF) and CP, whereas lower ( P < 0.05) GE compared with those from SKR. The SFM from MUL had higher DM, whereas lower CF and CP contents than SKR. In the first experiment, 216 21-d-old male broilers (Ross 308) were distributed over 8 test diets (4 ingredients × 2 locations) and 1 basal diet, with 4 replicates containing 6 birds each (9 × 4 × 6), in a complete randomized design to determine AME and AMEn. The results indicated higher ( P < 0.05) AME and AMEn in MUL CM than SKR. In the second experiment, 216 21-d-old male broilers (Ross 308) were raised in 36 cages (6 birds each) to determine SID of CP and AA in a complete randomized design. 8 test diets (4 ingredients × 2 locations) and a protein-free diet, with 4 replicates each, were tested. The SID of CP and some AA were higher ( P < 0.05) in MUL CM and RSM than SKR. The SKR GM had a higher ( P < 0.05) SID of CP, arginine, methionine, threonine, valine, and cysteine compared with that from MUL. The SFM from MUL had higher ( P < 0.05) SID of CP, arginine, histidine, methionine, valine, alanine, aspartate, cysteine, and serine than SKR. In conclusion, major differences do exist between CM, GM, RSM, and SFM from different locations in terms of nutrients, AME, digestible CP, and AA contents for male broilers.